2022
DOI: 10.1161/atvbaha.122.318151
|View full text |Cite
|
Sign up to set email alerts
|

Angiopoietin-1 Is Required for Vortex Vein and Choriocapillaris Development in Mice

Abstract: BACKGROUND: The choroidal vasculature, including the choriocapillaris and vortex veins, is essential for providing nutrients to the metabolically demanding photoreceptors and retinal pigment epithelium. Choroidal vascular dysfunction leads to vision loss and is associated with age-related macular degeneration and the poorly understood pachychoroid diseases including central serous chorioretinopathy and polypoidal choroidal vasculopathy that are characterized by formation of dilated pachyvessels thr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 81 publications
(150 reference statements)
0
5
0
Order By: Relevance
“…Non endothelial expression has been reported in skin (1), and in hematopoietic stem cells (26). In the mouse choroid, we and others have reported high EMCN expression that was attributed to endothelial cells (8-10). However, while EMCN expression is indeed high in choriocapillaries and other endothelial cells, at least some expression in these tissues originates in pericytes and fibroblasts.…”
Section: Discussionmentioning
confidence: 59%
See 1 more Smart Citation
“…Non endothelial expression has been reported in skin (1), and in hematopoietic stem cells (26). In the mouse choroid, we and others have reported high EMCN expression that was attributed to endothelial cells (8-10). However, while EMCN expression is indeed high in choriocapillaries and other endothelial cells, at least some expression in these tissues originates in pericytes and fibroblasts.…”
Section: Discussionmentioning
confidence: 59%
“…Due to its near-ubiquitous expression by capillary endothelial cells and the commercial availability of high-quality antibodies, EMCN is commonly used as an endothelial marker in tissues of the eye, kidney, lung, and elsewhere (7)(8)(9)(10)(11)(12). However, its widespread use as a molecular marker has not translated to research focus, and beyond its role in VEGF signaling and neutrophil adhesion, EMCN remains poorly understood (13).…”
Section: Introductionmentioning
confidence: 99%
“…The biological significance of Ang-2 has been experimentally demonstrated in terms of the effect of Tie2 activation on choroidal ischemia 38 . Additionally, knockout mice of Angptl1 in choroidal vessels have been shown to develop “pachychoroid (thick choroid)” 39 . Therefore, it is conceivable that Ang2 inhibition can improve choroidal circulation and ameliorate the morbidity caused by thickened choroidal thickness, further studies are needed to envelope the detailed mechanism.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies found that VEGF concentrations in the aqueous humor were lower in eyes with pachychoroid neovascularization than in those with drusen-associated MNV [ 25 , 26 ], whereas Ang-2 is elevated in eyes with pachychoroid features [ 26 ]. Moreover, knockout of Ang-1 in mice leads to a pachychoroid phenotype, indicating the role of angiopoietins in choroidal remodeling [ 27 ]. Taken together, our results support the hypothesis that dual Ang-2/VEGF-A inhibition potentiates choroidal vascular remodeling, which might give better results for Asian patients with nAMD, especially those associated with the pachychoroid phenotype.…”
Section: Discussionmentioning
confidence: 99%